NT3/TrkC Pathway Modulates the Expression of UCP-1 and Adipocyte Size in Human and Rodent Adipose Tissue - Bové, María; Monto, Fermi; Guillem-Llobat, Paloma; Ivorra, M Dolores; Noguera, M Antonia; Zambrano, Andrea; Sirerol-Piquer, M Salome; Requena, Ana Cristina; García-Alonso, Mauricio; Tejerina, Teresa; Real, José T.; Fariñas, Isabel; et al. (Frontiers in Endocrinology, 2021)
Neurotrophin-3 (NT3), through activation of its tropomyosin-related kinase receptor C (TrkC), modulates neuronal survival and neural stem cell differentiation. It is widely distributed in peripheral tissues (specially vessels and pancreas) and this ubiquitous pattern suggests a role for NT3, outside the nervous system and related to metabolic functions. The presence of the NT3/TrkC pathway in the adipose tissue (AT) has never been investigated. Present work studies in human and murine adipose tissue (AT) the presence of elements of the NT3/TrkC pathway and its role on lipolysis and adipocyte differentiation. qRT-PCR and immunoblot indicate that NT3 (encoded by NTF3) was present in human retroperitoneal AT and decreases with age. NT3 was also present in rat isolated adipocytes and retroperitoneal, interscapular, perivascular and perirenal AT. Histological analysis evidences that NT3 was mainly present in vessels irrigating AT close associated to sympathetic fibers. Similar mRNA levels of TrkC (encoded by NTRK3) and β-adrenoceptors were found in all ATs assayed and in isolated adipocytes. NT3, through TrkC activation, exert a mild effect in lipolysis. Addition of NT3 during the differentiation process of human pre-adipocytes resulted in smaller adipocytes and increased uncoupling protein-1 (UCP-1) without changes in -adrenoceptors. Similarly, transgenic mice with reduced expression of NT3 (Ntf3 knock-in lacZ reporter mice) or lacking endothelial NT3 expression (Ntf3flox1/flox2;Tie2-Cre+/0) displayed enlarged white and brown adipocytes and lower UCP-1 expression. Conclusions: NT3, mainly released by blood vessels, activates TrkC and regulates adipocyte differentiation and browning. Disruption of NT3/TrkC signaling conducts to hypertrophied white and brown adipocytes with reduced expression of the thermogenesis marker UCP-1